Calmodulin regulates the calcium homeostasis in mantle of Crassostrea gigas under ocean acidification - Xin, Xiaoyu; Liu, Chang; Liu, Zhaoqun; Zhang, Yukun; Gao, Yuqian; Zhu, Ting; Wang, Lingling; Song, Linsheng (Frontiers in Marine Science, 2022)
The biosynthesis of shell is a complicated calcification process in the marine bivalve, which can be severely impacted by ocean acidification (OA). Calmodulin (CaM) is a pivotal calcium regulator and thought to be crucial for calcification. In the present study, a CaM (designated CgCaM) with calcium-binding activity was identified from the Pacific oyster Crassostrea gigas with the objective to understand its possible role in the regulation of calcium homeostasis under acidification treatment. The open reading frame (ORF) of CgCaM was of 474 bp encoding a 17.5 kDa protein with four continuous EF-hand domains. CgCaM shared high similarity with CaMs from other invertebrates and vertebrates. The mRNA transcript of CgCaM was constitutively expressed in all detected tissues with the higher expression level in mantle, especially highest in the middle fold of the three folds of mantle. CgCaM was found to be mainly distributed in the mantle epithelium. When the oysters were exposed to acidified seawater, the expression level of CgCaM in the middle fold of mantle and the content of Ca2+ in this fold both decreased significantly. These results collectively suggested that CgCaM was involved in the regulation of calcium homeostasis in the middle fold of mantle under acidification treatment.